2022
DOI: 10.3390/metabo12111139
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Genetic Variants and Metabolites Associated with Rapid Estimated Glomerular Filtration Rate Decline in Korea Based on Genome–Metabolomic Integrative Analysis

Abstract: Identifying the predisposing factors to chronic or end-stage kidney disease is essential to preventing or slowing kidney function decline. Therefore, here, we investigated the genetic variants related to a rapid decline in the estimated glomerular filtration rate (eGFR) (i.e., a loss of >5 mL/min/1.73 m2 per year) and verified the relationships between variant-related diseases and metabolic pathway signaling in patients with chronic kidney disease. We conducted a genome-wide association study that included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…25 Lee et al reported that MARCHF1, a regulator of lipid metabolism and glucose tolerance, could potentially contribute to the progression of CKD by causing oxidative stress in the proximal tubular endoplasmic reticulum. 26,27 TA B L E 1 Genome-Wide Association Studies in kidney function.…”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Lee et al reported that MARCHF1, a regulator of lipid metabolism and glucose tolerance, could potentially contribute to the progression of CKD by causing oxidative stress in the proximal tubular endoplasmic reticulum. 26,27 TA B L E 1 Genome-Wide Association Studies in kidney function.…”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 99%
“…25 Lee et al reported that MARCHF1, a regulator of lipid metabolism and glucose tolerance, could potentially contribute to the progression of CKD by causing oxidative stress in the proximal tubular endoplasmic reticulum. 26,27 Hereditary CKD refers to CKD that is caused by genetic factors. With the continuous advancement of genetic sequencing, candidate genes for hereditary CKD have been steadily discovered, thus expanding the scope of this disease.…”
Section: The Theory Of the Kidney As The Foundation Of Heritability W...mentioning
confidence: 99%